2018
DOI: 10.3390/app8050732
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Modelling of Shrinkage and Creep of Reactive Powder Concrete

Abstract: The objective of this study was to examine the shrinkage and creep of reactive power concrete (RPC) with different steel fibre contents (0%, 1% and 2% by volume). A total of 37 RPC specimens were prepared and tested for compression strength, elastic modulus, shrinkage, and creep. In addition, different axial stress ratios (0.2, 0.3 and 0.4) were used in the creep tests. Furthermore, the accuracy of the ACI 209-82 model, CEB-FIP 90 model, B3 model, and GL 2000 model for predicting the shrinkage and creep of RPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…In analysing the results presented in this paper, as well as the most recent literature in the field of 3D concrete printing, it would be prudent to consider future possible research avenues regarding deformations in production materials, as well as to analyse methods of predicting shrinkage in 3DCP [52,53]. The research shows the influence of the types of curing method on the shrinkage of 3D-printed concrete.…”
Section: Future Workmentioning
confidence: 95%
“…In analysing the results presented in this paper, as well as the most recent literature in the field of 3D concrete printing, it would be prudent to consider future possible research avenues regarding deformations in production materials, as well as to analyse methods of predicting shrinkage in 3DCP [52,53]. The research shows the influence of the types of curing method on the shrinkage of 3D-printed concrete.…”
Section: Future Workmentioning
confidence: 95%
“…There are different models and equations to account for and predict shrinkage in concrete and similar cementitious systems. The most common ones include the ACI 209-82 model [83,84], CEB-FIP model [85], and B3 model [85][86][87]. Generally, shrinkage is associated with the drying of the surface as a result of evaporation and bleeding, which increase pore pressure and the radius menisci which induces stresses in the pore.…”
Section: Materials Drying and Curingmentioning
confidence: 99%
“…Chen et al [9] performed an analysis and modelling of the shrinkage and creep of reactive powder concrete (RPC) with various steel fiber contents. It was revealed that the compressive strength and modulus of elasticity increased with increasing steel fiber content, contrary to shrinkage and creep.…”
Section: Long-term Behavior Of Recycled Aggregate Concretementioning
confidence: 99%